Fractal method of calculation whole-cell dimension to identify the risks of recurrent myocardial infarction by analyzing patient’s scattergrams - O.I. Antipov; P.A. Lebedev; A.A. Matyushkina; V.A. Neganov (Физика волновых процессов и радиотехнические системы, 2015)
In article we use calculation of the Minkowskis fractal dimension for a scattergram that are based on pulsograms. The features of the application of fractal techniques to short pulsograms total duration of no more than five minutes. The paper studied the fractal dimension of the two groups of patients: myocardial infarction and with repeated myocardial infarction. It is shown that the statistical relationship between the fractal dimensions scattergram in patients with recurrent myocardial infarction.